Qualitative study of barriers and facilitators of health entrepreneurship in rural and semirural communities of Armenia - Astghik Atanyan; Karine Markosyan; Anahit Demirchyan; Hratchia Lylozian; Aida Giloyan; Lusine Kocharyan; Tsovinar Harutyunyan (James Cook University, 2022)
Introduction: Low- and middle-income countries often face the issue of unequal distribution of healthcare services and human resources between rural and urban areas. Globally, there are many factors negatively affecting the willingness of physicians to work in remote and rural areas, such as low wages, poor living conditions, poorer and sicker patients, suboptimal equipment and supplies, and a lack of quality infrastructure and transportation. Methods: This study explored the perceptions of barriers and facilitators of medical entrepreneurship and the impact of medical entrepreneurship on the served communities among the owners of private medical practices in rural and semirural areas of Armenia. The researchers conducted qualitative in-depth interviews with the 13 owners of 12 private practices. The interviews were transcribed in the original language (Armenian). Only the quotes were translated into English. The direct content analysis approach was used for analyzing textual data. Results: The findings of the study suggest that high investment cost, intense competition with state facilities, unfavorable laws and regulations, and a lack of entrepreneurship and healthcare quality assurance skills were perceived as barriers to establishing and running private healthcare practices. The dissatisfaction of healthcare providers with their work conditions in state facilities, the instability of the job market in Armenia, and the development of clear marketing strategies by the entrepreneurs facilitated opening and operating private practices. All of the interviewees felt that their practices had a positive impact on the communities they served, in terms of creating new jobs and introducing up-to-date and in-demand services into these communities. Conclusion: The study recommended providing potential entrepreneurs with training in entrepreneurship and healthcare quality assurance and mentorship opportunities, as well as with tools to support financing their enterprises.